Trends in agricultural water resources - Inocencio, Arlene B. (Animo Repository, 2014)
One of the pathways through which climate change will be felt is its impact on water resources (WEPA 2012). This includes increased risk in the form of excess water, water shortages, and poor water quality, and disruptions to freshwater ecosystems due to higher water temperatures, increased intensity and duration of precipitation, longer periods of low flows, and higher operating costs (Kundzewicz et al. 2007). Dependence on and overexploitation of groundwater can result from the unreliability of surface water supplies, while at the same time changes in precipitation patterns increase the incidence of flooding. Increased water risks and growing uncertainty about future conditions are already exacerbating existing water security challenges in the Philippines and have implications for water related planning, management, and investment decisions. Adapting to new circumstances will require knowledge-based investment strategies and adaptive water governance, taking into account climate variability and minimizing potentially costly mismatches between water systems and the future climate. This chapter outlines trends in water resource investments and agricultural water uses, focusing on irrigation projects, for the purpose of examining the preparedness of the agricultural sector to respond to the adverse impacts of climate change. While the literature on these impacts is mixed, lack of action could be more costly than a proactive, anticipatory approach. The increased recognition of the need to consider and mainstream the implications of climate change in government initiatives should be matched by increased preparation rather than a cursory or "business as usual" response. The next section outlines potential climate change adaptation strategies relating to water and irrigation. Thereafter, the climate change strategy of the National Irrigation Administration (NIA) is presented, followed by a discussion of trends in public investments in irrigation at national and subnational levels, which reflect planning, management, and decision making about agricultural water allocation and use. The chapter concludes with policy implications.